2020
DOI: 10.1055/s-0040-1709143
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Reconstruction of the Maxilla and Palate

Abstract: Maxillary defects commonly present following surgical resection of oncologic processes. The use of rotational and free flaps has largely replaced the use of prosthetic options for hard palate and maxillary reconstruction, but prostheses remain a useful tool. Prosthetic devices may be invaluable in patients considered poor candidates for surgical reconstruction secondary to poor vascularity, need for postoperative radiation, or medical comorbidities that place them at high risk for healing following reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
9
0
3
Order By: Relevance
“…The results of the available studies clearly prove the effectiveness of the use of obturators in patients who have undergone maxillectomy [21,22]. The main disadvantage of this solution is severe pain associated with the initial period of use.…”
Section: Discussionmentioning
confidence: 86%
“…The results of the available studies clearly prove the effectiveness of the use of obturators in patients who have undergone maxillectomy [21,22]. The main disadvantage of this solution is severe pain associated with the initial period of use.…”
Section: Discussionmentioning
confidence: 86%
“…At present, there is no unified standard method for the repair of palatal defect. According to the location and size of the fistula hole, different repair methods, such as prosthetic reconstruction, local rotating mucoperiosteal flap, free skin flap, lingual flap, and buccal muscle and mucosal flap, have been reported 10,12–15 . A retrospective study by Bonanthaya et al 16 showed that the quality and condition of adjacent tissues may be the main regulating factors in the selection of surgical repair and prognosis of palatal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…• For maxillectomized patients, irrigation with saline solution (or salt and sodium bicarbonate) through the nasal cavity is indicated, as well as oral washing several times a day 43 .…”
Section: Daily Carementioning
confidence: 99%